Tendencias y retos de dos universidades públicas latinoamericanas: (Unam y Unc) ante las nuevas políticas publicas para la educación superior = Tendencies and challenges of Latin American public universities: (UNAM and UNC) in relation to the new public policies for higher education - Flachs, María Cristina Vera de; Sierra, María Teresa de (Educação)
This article performs a comparative analysis of the effects of the new public policies for Higher Education applied internationally, particularly at two Latin American universities, UNAM and UNC, since the end of the 1980s. The implications of applying similar models were also studied specifically for each case, taking into account that both dealt with common themes: academic and institution evaluation and accreditation, as well as internationalization. On the other hand, we referred to how the institutional histories and academic cultures mediated the management models and the behavior of the players involved, with variable effects on how knowledge is organized and its connection to society. In both cases, the classical model of education underwent a crisis, due to massification, reduction of the government budget and greater control of investment costs, leading institutions to seek other sources of funding and to generate mechanisms to strengthen their social responsibility within a framework of autonomy